A VARBRUL Analysis on The Reporting Verb Propose in Electrical Engineering Research Articles - Thong Vi Nguyen (International Journal of Language Teaching and Education, 2018)
Choosing an appropriate reporting verb is not only a technique to report a claim but also a tool to imply the writer’s stance or attitude towards the claim. The manner in which the reporting verb is employed can reflect the writer’s underlying implication. By using a variationist framework, this study is an in-depth investigation on how reporting verbs are affected in Electrical engineering research articles, taking propose as a variation. With the assistance of VARBRUL program, 397 tokens from 160 Electrical research articles were analyzed. Past tenses of propose was selected as an application value. The results show that time periods that the articles are published and verb voices are two factors independent from the application value. Meanwhile, tense choice of the verb has a significant correlation with journal editions and verb types. In different journals, frequency of propose used in past tenses can vary, and a significant proportion of self-reporting propose is used in past tense. Regardless the limitation of sample size and verb types, the study is potential in analyzing reporting verb from the sociolinguistic approach in future.